ATRIBUTOS PRESENTES NA AVALIAÇÃO DA QUALIDADE DE SERVIÇOS NO SETOR BANCÁRIO DE TRÊS PASSOS - Graffunder, Jonas L.; Klein, Claiton; Câmara, Franciele; Schmiddel, Vanessa V.; Krohn, Marciani K.; Zamberlam, Luciano (Salão do Conhecimento, 2013)
Resumo